2000
DOI: 10.23818/limn.19.08
|View full text |Cite
|
Sign up to set email alerts
|

The rotifers of Spanish reservoirs: ecological, systematical and zoogeographical remarks

Abstract: This article covers the rotifer data from a 1987/1988 survey of one hundred Spanish reservoirs. From each species brief information is given, focused mainly on ecology, morphology, zoogeography and distribution both in Spain and within reservoirs. New autoecological information on each species is also established giving conductivity ranges, alkalinity, pH and temperature for each. Original drawings and photographs obtained on both optical and electronic microscopy are shown of the majority of the species found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…García-Chicote (2015) reportan a este rotífero como propio de embalses eutróficos; no obstante, este no es el caso del embalse Punchiná. K. cochlearis es uno de los rotíferos ampliamente distribuidos en los sistemas tropicales, euritérmico, que se alimenta de forma indiscrimida de una gran cantidad de algas, así como de detritos y bacteríoplancton (De Manuel, 2000).…”
Section: Daphnia Ambiguaunclassified
See 1 more Smart Citation
“…García-Chicote (2015) reportan a este rotífero como propio de embalses eutróficos; no obstante, este no es el caso del embalse Punchiná. K. cochlearis es uno de los rotíferos ampliamente distribuidos en los sistemas tropicales, euritérmico, que se alimenta de forma indiscrimida de una gran cantidad de algas, así como de detritos y bacteríoplancton (De Manuel, 2000).…”
Section: Daphnia Ambiguaunclassified
“…Adicionalmente, se ha postulado (Vásquez et al, 1991) que esta especie se ve favorecida por una mayor disponibilidad de partículas alimenticias, lo cual puede estar asociado con su dominancia numérica en San Lorenzo, puesto que existe una oferta alimenticia de diversas clases de fitoplancton que son ampliamente palatables para el zooplancton. K. cochlearis ha dominado la densidad en diversos embalses colombianos, entre ellos, Punchiná (Villabona- González, 2012), probablemente por ser eurifágico (amplia plasticidad alimenticia) y presentar amplios rangos de tolerancia a las variaciones ambientales (de Manuel, 2000). Además, los géneros Keratella y Polyarthra presentan un aparato masticador virgado, que les permite succionar selectivamente fluidos celulares (Nogrady et al, 1993).…”
Section: Zooplanctonunclassified
“…El-Shabrawy & Germoush (2014) reported comparable results from a eutrophic lake in Manzalah. Although Inaotombi et al (2016) reported K. quadrata to be a thermophilic species, it has also been described as tolerant of a wide range of temperature and mineralization conditions (De Manuel Barrabin, 2000). It has also been reported in spring from a dam in northern Algeria (Bidi-Akli et al, 2014).…”
Section: Biotic Variablesmentioning
confidence: 99%
“…m -3 . Rotifers are also known to be an important link between the microbial loop and higher trophic levels in the ecosystems [7]. Therefore, many authors suggest that zooplankton should be used as an indicator in assessing the trophic state of lakes [2,3,6,8].…”
Section: Introductionmentioning
confidence: 99%